2018
DOI: 10.1111/inm.12439
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff‐led behavioural group intervention in psychiatric in‐patient care: Patient and staff experiences

Abstract: A promising intervention in mental health in-patient care is behavioural activation (BA). Interventions based on BA can be used by mental health nurses and other staff members. The aim of this study was to evaluate patients' and staff members' experiences of a nursing staff-led behavioural group intervention in mental health in-patient care. The intervention was implemented at three adult acute general mental health in-patient wards in a public hospital setting in Sweden. A self-administrated questionnaire, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
(109 reference statements)
2
9
0
Order By: Relevance
“…They predominantly reported positive experiences, as in previous research on STR (Salberg et al . 2018), where the programme was evaluated in a similar clinical context but in a smaller local hospital setting. Nursing staff reported positive experiences of the contents and integration of the programme into nursing practice and the contribution to improvement of nursing care was rated as high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They predominantly reported positive experiences, as in previous research on STR (Salberg et al . 2018), where the programme was evaluated in a similar clinical context but in a smaller local hospital setting. Nursing staff reported positive experiences of the contents and integration of the programme into nursing practice and the contribution to improvement of nursing care was rated as high.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a recovery-oriented nursing programme is Steps Towards Recovery (STR), focusing on the individual recovery process while taking advantage of the benefits of a group format. The programme was first developed in a rural hospital setting in Sweden (Folke et al 2015b) and is based on behavioural activation (Folke et al 2015b;Salberg et al 2018). Behavioural activation is a psychological intervention aiming to reduce rumination and avoidance behaviour and increase consumer participation in activities that promote positive reinforcement (Kanter et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Molin et al (2020) concluded that joint activities for patients and staff in PIC fostered relationships but also felt burdensome to staff due to struggles with time and disagreements among staff members. Further, Salberg et al (2018), who evaluated a nursing staff-led behavioural group intervention in PIC, reported that nursing staff experienced patients as more involved in their care and that they came closer to the patients and the atmosphere on the unit improved. Negative effects included staff members' negative attitudes and challenges in both conversations and interactions during the sessions.…”
Section: Discussionmentioning
confidence: 99%